The Role of Zakat in Social Protection in Islamic Developing Countries: A Contributing Instrument - Akmal Salim Ruhana (SMART Insight, 2019)
Social protection has become an essential agenda in the world countries, either in developed or developing ones. It implements in varied ways and correlates with the 2030 Sustainable Development Goals (SDGs) targets, especially on poverty reduction agenda. Meanwhile, in Islamic developing countries, there is a religious-based concept, so-called zakat, which is conceptually similar with and functionally underpin social protection programs. This paper attests its similarity through a comparative study with Australian social protection concepts. Furthermore, the paper elaborates the potencies of zakat contribution on social protection particularly on addressing the poor and the vulnerable as social protection programs do. In general, the zakat system offers a huge potential of the fund for social protection, but a kind of mismanagement or such inefficiency in zakat institution, as well as political reluctance, can challenge it. This paper recommends a combination or integration between zakat system and the existing social protection system for the better social protection program and on amplifying the effect of these contributing instruments to the needy.